2010
DOI: 10.4314/wajae.v15i1.49427
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Water Quality of the Oti River in Ghana

Abstract: Oti river, an important tributary of the Volta lake in Ghana, was chosen as a case study to investigate the variations in the quality of its water at different locations. This was necessitated by the people's reliance on the river for their domestic and agricultural water use. Composite water samples drawn from some sections of the Oti river were analysed in the laboratory for certain parameters to enable assessment of water quality. The observed results of the laboratory analyses are compared with the 2003 Gh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 4 publications
(1 reference statement)
2
14
1
Order By: Relevance
“…The high levels of these metals in this vegetable might be as a result of the use of pesticides and herbicides and irrigated with tin mine water [60]. This also agrees with the findings that, the application of large volumes of partially treated or untreated wastewater in some parts of Africa has adversely affected both surface water bodies and the urban and peri-urban farmers using these water bodies as sources of irrigation [61].…”
Section: Heavy Metals Accumulation In Cultivated Vegetablessupporting
confidence: 87%
“…The high levels of these metals in this vegetable might be as a result of the use of pesticides and herbicides and irrigated with tin mine water [60]. This also agrees with the findings that, the application of large volumes of partially treated or untreated wastewater in some parts of Africa has adversely affected both surface water bodies and the urban and peri-urban farmers using these water bodies as sources of irrigation [61].…”
Section: Heavy Metals Accumulation In Cultivated Vegetablessupporting
confidence: 87%
“…The TC recorded in this study was similar to values observed by Abdul-Razak et al (2009) who recorded TC levels ranging from 770 -8820 cfu/100 ml. The high TC counts observed at the control site in this study may be due to anthropogenic activities such as tourism and sewage from the villages around the area.…”
Section: Microbiological Quality Of the Study Areasupporting
confidence: 90%
“…The values recorded were slightly higher but comparable to findings by Asase (2013) who had mean value of 28.50 ± 0.04 mg/l on the Volta Lake in Akosombo. When compared with the values of 34 -52 mg/l showed by Abdul-Razak et al (2009) in the Oti arm of the Volta Lake, alkalinity values during this study was lower. Samah (2012) also recorded alkalinity values of 12.68 -16.05 mg/l in the Asukawkaw River.…”
Section: Fish Cage Culture Impact On Water Qualitycontrasting
confidence: 50%
“…Our findings suggest that water in River Offin is softer than water from other rivers in Ghana e.g. River Oti [32]. Turbidity was highest at the semi-closed canopy.…”
Section: Discussionmentioning
confidence: 62%